United Republic of Tanzania : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper presents Joint Staff Advisory Note on the United Republic of Tanzania's Poverty Reduction Strategy. Tanzania has already achieved the Millennium Development Goals for universal primary education, and significant progress has been made in reducing income poverty, malnutrition, child mortality, and gender inequality in primary education. Improving agricultural productivity requires making progress with implementing the agricultural sector strategy, promoting innovation, value addition and crop and region-specific approaches, and removing obstacles to doing business.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet